Acute Leukemia in A Young Female Adult Presenting for Care in A Resource Constrained Setting - Mwizabi, Simakando A.; Musuka, Brian; Mwape, Celine; Mulenga, Audrey; Mweene, Mutale; Maliko, Catherine; Maksoud, Gamal; Chimese, Mwinsa; Zulu, Mabvuto; Chinkoyo, Sebastian; Nyirenda, Christopher (Clinical Medicine And Health Research Journal, 2023)
Background: Acute leukemia is a rare malignant disorder arising from an abnormal proliferation of hematopoietic precursor cells. With advances in the management of leukemia, patients of acute leukemia have high chances of achieving adequate remission and survival. However, due to late presentation, diagnosis and treatment, the disease has significantly contributed to high morbidity and mortality especially in resource limited settings. Method: A comprehensive history and physical examination was taken, coupled with literature review. Various rationale for each intervention and recommended interventions unavailable in our setting were noted. Results: Early diagnosis and treatment of leukemia and its complications is a major public health concern for which the general public needs to be educated on. In this case report, material and human resource constraints in our setting may contribute towards the patient’s poor clinical outcome. Conclusion and recommendations: Acute leukemia is a manageable disorder provided the availability of appropriate resources and interventions being implemented early. There is therefore need to equip our health facilities and personnel with resources towards early clinical detection, diagnosis and treatment which measures are essential for successful management and prevention of unwanted complications.